Low carbon economic dispatch of power system at multiple time scales considering GRU wind power forecasting and integrated carbon capture - Ding, Can; Zhou, Yiyuan; Pu, Guang; Zhang, Hongrong (Frontiers in Energy Research, 2022)
To achieve carbon neutrality in electricity, measures such as increasing the share of renewable energy sources such as wind power and achieving more accurate and faster wind power forecasting, and low carbon retrofitting of thermal power units are all important to achieve the goal. Firstly, the GRU prediction algorithm was used to forecast wind power, which performed well in terms of prediction accuracy and model training speed. Then, we continue to fully utilize the source-side low-carbon characteristics by installing flue gas bypass systems and liquid storage in carbon capture plants to form an integrated carbon capture plant operation, thereby reducing carbon emissions and the proportion of abandoned wind. Secondly, a three-level low carbon economic dispatch model is developed to optimise the system wind and rotating reserve ratios by combining wind power forecasts on different time scales. Finally, a case study is carried out using the optimised IEEE-39 nodal system. The results show that the proposed three-stage integrated dispatching method can make full use of wind energy and achieve the goal of economic dispatching of the power system.